Geometric tuning of thermal conductivity in three-dimensional anisotropic phononic crystals. Issue 37 (18th July 2016) - Wei, Zhiyong; Wehmeyer, Geoff; Dames, Chris; Chen, Yunfei
Abstract : Increasing key length scales of a three-dimensional anisotropic phononic crystal can reduce the thermal conductivity in certain directions. Abstract : Molecular dynamics simulations are performed to investigate the thermal transport properties of a three-dimensional (3D) anisotropic phononic crystal consisting of silicon nanowires and films. The calculation shows that the in-plane thermal conductivity is negatively correlated with the out-of-plane thermal conductivity upon making geometric changes, whether varying the nanowire diameter or the film thickness. This enables the anisotropy ratio of thermal conductivity to be tailored over a wide range, in some cases by more than a factor of 20. Similar trends in thermal conductivity are also observed from an independent phonon ray tracing simulation considering only diffuse boundary scattering effects, though the range of anisotropy ratios is smaller than that obtained in MD simulation. By analyzing the phonon dispersion relation with varied geometric parameters, it is found that increasing the nanowire diameter increases the out-of-plane acoustic phonon group velocities, but reduces the in-plane longitudinal and fast transverse acoustic phonon group velocities. The calculated phonon irradiation further verified the negative correlation between the in-plane and the out-of-plane thermal conductivity. The proposed 3D phononic crystal may find potential application in thermoelectrics, energy storage, catalysis and sensing applications owing to its widely tailorable thermal conductivity.